Lnc-HSD17B11-1:1 Functions as a Competing Endogenous RNA to Promote Colorectal Cancer Progression by Sponging miR-338-3p to Upregulate MACC1 - Zhang, Wei; Wang, Bo; Wang, Quan; Zhang, Zhen; Shen, Zhanlong; Ye, Yingjiang; Jiang, Kewei; Wang, Shan (Frontiers in Genetics, 2020)
ABSTRACT BACKROUND Long noncoding RNAs (lncRNAs) play pivotal roles in various kinds of human diseases, especially in cancer. However, regulatory role, clinical significance and underlying mechanisms of lncRNAs in colorectal cancer (CRC) liver metastasis still remain largely unknown. This study aimed to report a novel lncRNA, lnc-HSD17B-11:1, and its functional role in CRC progression. MATERIALS AND METHODS Differentially expressed lnc-HSD17B11-1:1 was screened and identified from a lncRNA profile microarray. Quantitative real-time PCR was used to determine the expression levels and prognostic values of lncRNA in CRC cohorts. In vitro and in vivo functional experiments were performed to investigate the effects of lnc-HSD17B11-1:1 on tumor growth and metastasis in CRC. Mechanistically, Base Scope, bioinformatics analyses, dual luciferase reporter assay and RNA immunoprecipitation experiments were performed to confirm the association of lnc-HSD17B11-1:1 and miR-338-3p. Dual luciferase reporter assay, qRT-PCR and western blot analysis were performed to assess the relationships among lnc-HSD17B11-1:1, miR-338-3p and MACC1. RESULTS Evidently up-regulation of lnc-HSD17B11-1:1 in CRC primary tissues was correlated with the depth of invasion(p=0.043), clinical stage(p=0.027), distant metastasis(p=0.003) and poor prognosis of patients with CRC. lnc-HSD17B11-1:1 promoted CRC cell proliferation, mobility and invasion in vitro and in vivo. Mechanistic analysis revealed that lnc-HSD17B11-1:1 may act as a competing endogenous RNA (ceRNA) by acting as a sponge for miR-338-3p to upregulate the expression of MACC1. CONCLUSION These findings suggest that lnc-HSD17B11-1:1 promotes CRC progression through lnc-HSD17B11-1:1/miR-338-3p/MACC1 axis and this might serve as a new diagnostic marker or target for treatment of CRC.